Analisis Konsumsi Bahan Bakar Pada Alat Berat Volvo ADT A35C 45 Ditinjau Dari Pengaruh Kerusakan Nozzle Di PT Firman Ketaun - TIMUR, RIZKY; BISMANTOLO, PUTRA (UNIB Press, 2021)
Analysis of Fuel Consumption in Volvo ADT A35C Heavy Equipment 45 In terms of the effect of nozzle damage at PT Firman Ketaun. One of the components contained in the Volvo ADT A35C 45, which affects the combustion system is the injector, the purpose of this study is to determine the factors that cause damage to the Volvo ADT A35C 45 nozzle on fuel consumption. This study uses an injector tester to check fuel fogging, then to calculate fuel consumption where data collection is carried out before the nozzle component is replaced and after the replacement is made. For good fogging of the nozzle components where changes have been made, the pressure is 260-270 bar but In the data from the results of the condensation process, it was found that at the lowest pressure on the old 4 nozzle test, where the pressure was 220-230 bar and bad fogging occurred thirst for the nozzle components, and the highest pressure was obtained in the old 6 nozzle test, where the holes were clogged due to crust on nozzle surface. From these data, it is also found that the difference in fuel consumption of 0.64 liters, multiplied by the length of time operating in ± 250 months (working hours) x Rp. 7,680.00 (costs saved per hour) is Rp1,920,000.00. If multiplied by one year / 12 months, the company will save IDR 23,040,000.00. Then if it is multiplied by the total Volvo ADT A35C units operating at pt Firman per year as many as ± 23 units, the company can save fuel consumption costs for one year, namely Rp.529,920,000.00